The role of customary governance systems in enhancing local democracy the case of Ghana - Sackey, Margaret (2012)
Local governance, decentralization, and democracy are components of the Ghanaian traditional chieftaincy institution. This institution in the past engendered participatory democracy, good governance, and social protection but is currently challenged by formal decentralization of public administration. Although the institution has remained intact, its functions have gone through several paradigm shifts both during the colonial and the post-independence eras of Ghana. Currently, the chieftancy does not form part of the formal local government administration structure. In an enigmatic form, it maintains an informal and sacrosanct niche in local governance. There is a need for redefinition and clarification of the roles of the chieftancy institution within the nexus of traditions, demands of good governance, and modern local democracy to enable it to provide a complementary conduit for effective and efficient local governance for development.
Keywords: Decentralization in government; Local government -- Ghana; Democracy -- Ghana